2008
DOI: 10.1099/vir.0.2008/003558-0
|View full text |Cite
|
Sign up to set email alerts
|

The p59 oligoadenylate synthetase-like protein possesses antiviral activity that requires the C-terminal ubiquitin-like domain

Abstract: Viral infection of mammalian cells prompts the innate immune system to initiate an antiviral response. The recognition of the virus triggers several antiviral signalling pathways, which among others include the family of 29-59 oligoadenylate synthetase (OAS) proteins. The p59 protein encoded by the OAS-like (OASL) gene is an atypical member of the OAS family in the sense that it lacks the characteristic 29-59 oligoadenylate synthetase activity. We decided to investigate the putative antiviral activity of p59 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 21 publications
2
43
0
Order By: Relevance
“…In response to 10 Gy single radiation exposure, five immune genes were also upregulated to two- to threefold (Table 1). Out of these 5, two genes, IFITMI and OASL (19, 20), were upregulated in multifractionated treatment. The remaining three genes, S100A9, FABP4 and HLA-DMA , are involved in inflammatory secretions by T cells or macrophages and peptide exchanges (2426) and were unique for single-dose treatment.…”
Section: Resultsmentioning
confidence: 99%
“…In response to 10 Gy single radiation exposure, five immune genes were also upregulated to two- to threefold (Table 1). Out of these 5, two genes, IFITMI and OASL (19, 20), were upregulated in multifractionated treatment. The remaining three genes, S100A9, FABP4 and HLA-DMA , are involved in inflammatory secretions by T cells or macrophages and peptide exchanges (2426) and were unique for single-dose treatment.…”
Section: Resultsmentioning
confidence: 99%
“…OASL is an atypical member of the OAS family, because it lacks the characteristic 2Ј-5Ј OAS activity shared by OAS1, OAS2, and OAS3 (44). Long known as an ISG, the antiviral role of OASL p59 had not been recognized until the recent observation that overexpression of OASL inhibited encephalomyocarditis virus replication (45). Very recently, it was shown that viral induction of OASL depends on IRF3 (46).…”
Section: Induction Of Zap and Other Cellular Mrnas By A Constitutivelmentioning
confidence: 99%
“…In OAS1, the core OAS unit includes the first 346 N-terminal amino acids (52). In addition to these three forms, OASL (OAS like protein) has one OAS unit and two ubquitin-like domains but is devoid of the OAS enzymatic activity (53,54). convert into the active forms via oligomerization (55).…”
Section: Rna Binding and Oas Activationmentioning
confidence: 99%